Remembering the present: mindfulness in Buddhist Asia - Cassaniti, Julia (Cornell Studies in Security Affairs, 2018)
What is mindfulness, and how does it vary as a concept across different cultures? How does mindfulness find expression in practice in the Buddhist cultures of Southeast Asia? What role does mindfulness play in everyday life? J. L. Cassaniti answers these fundamental questions and more in her engaged ethnographic investigation of what it means to "remember the present" in a region strongly influenced by Buddhist thought.Focusing on Thailand, Sri Lanka, and Myanmar, Remembering the Present examines the meanings, practices, and purposes of mindfulness. Using the experiences of people in Buddhist monasteries, hospitals, markets, and homes in the region, Cassaniti shows how an attention to memory informs how people live today and how mindfulness is intimately tied to local constructions of time, affect, power, emotion, and selfhood. By looking at how these people incorporate Theravada Buddhism into their daily lives, Cassaniti provides a signal contribution to the psychological anthropology of religious experience.Remembering the Present heeds the call made by researchers in the psychological sciences and the Buddhist side of mindfulness studies for better understandings of what mindfulness is and can be. Cassaniti addresses fundamental questions about selfhood, identity, and how a deeper appreciation of the many contexts and complexities intrinsic in sati (mindfulness in the Pali language) can help people lead richer, fuller, and healthier lives. Remembering the Present shows how mindfulness needs to be understood within the cultural and historical influences from which it has emerged.